The study of Forest Hara Biosphere Reserve in coast of Persian Gulf and the importance of heavy metal accumulation; Case study: feathers of great cormorant - MIR MEHRDAD MIRSANJARI; FARNAZ SHEYBANIFAR; FARSHID ARJMAND (Nusantara Bioscience, 2014)
Abstract. Mirsanjari MM, Sheybanifar F, Arjmand F. 2014. The study of forest Hara Biosphere Reserve in coast of Persian Gulf and the importance of heavy metal accumulation; Case study: feathers of great cormorant. Nusantara Bioscience 6: 159-164. In recent years, concerns about the long term effects of heavy metals as environmental polluters have arisen, since considerable quantities of heavy metals have been released into the environment as a result of extensive human activities. Heavy metal has been determined as a serious threat to the stability of ecosystems. In this study, we examined the levels of zinc‚ copper‚ lead, and cadmium in the feathers of twenty great cormorants (Phalacrocorax carbo), collected from Hara Biosphere Reserve during November and December in 2012. The results revealed that the mean concentration of heavy metals in the feathers of males is significantly higher than females (P < 0.05). In addition‚ no significant difference was observed in heavy metal concentration between juvenile and adult birds. Moreover, according to the results, the high concentration of heavy metals in some samples indicated this fact that birds are potentially exposed to the risk of heavy metals in their habitat.